Free resolutions of Dynkin format and the licci property of grade 3 perfect ideals - Christensen, Lars Winther; Veliche, Oana; Weyman, Jerzy (MATHEMATICA SCANDINAVICA, 2019)
Recent work on generic free resolutions of length 3 attaches to every resolution a graph and suggests that resolutions whose associated graph is a Dynkin diagram are distinguished. We conjecture that in a regular local ring, every grade 3 perfect ideal whose minimal free resolution is distinguished in this way is in the linkage class of a complete intersection.